이동 평균 기반 동적 시간 와핑 기법을 이용한 시계열 키워드 데이터의 분류 성능 개선 방안 - 정도헌; Jeong, Do-Heon (Chŏngbo Kwalli Hakhoechi, 2019)
This study aims to suggest an effective method for the automatic classification of keywords with similar patterns by calculating pattern similarity of temporal data. For this, large scale news on the Web were collected and time series data composed of 120 time segments were built. To make training data set for the performance test of the proposed model, 440 representative keywords were manually classified according to 8 types of trend. This study introduces a Dynamic Time Warping(DTW) method which have been commonly used in the field of time series analytics, and proposes an application model, MA-DTW based on a Moving Average(MA) method which gives a good explanation on a tendency of trend curve. As a result of the automatic classification by a k-Nearest Neighbor(kNN) algorithm, Euclidean Distance(ED) and DTW showed 48.2% and 66.6% of maximum micro-averaged F1 score respectively, whereas the proposed model represented 74.3% of the best micro-averaged F1 score. In all respect of the comprehensive experiments, the suggested model outperformed the methods of ED and DTW. 본 연구는 시계열 특성을 갖는 데이터의 패턴 유사도 비교를 통해 유사 추세를 보이는 키워드를 자동 분류하기 위한 효과적인 방법을 제안하는 것을 목표로 한다. 이를 위해 대량의 웹 뉴스 기사를 수집하고 키워드를 추출한 후 120개 구간을 갖는 시계열 데이터를 생성하였다. 제안한 모델의 성능 평가를 위한 테스트 셋을 구축하기 위해, 440개의 주요 키워드를 8종의 추세 유형에 따라 수작업으로 범주를 부여하였다. 본 연구에서는 시계열 분석에 널리 활용되는 동적 시간 와핑(DTW) 기법을 기반으로, 추세의 경향성을 잘 보여주는 이동평균(MA) 기법을 DTW에 추가 적용한 응용 모델인 MA-DTW를 제안하였다, 자동 분류 성능 평가를 위해 k-최근접 이웃(kNN) 알고리즘을 적용한 결과, ED와 DTW가 각각 마이크로 평균 F1 기준 48.2%와 66.6%의 최고 점수를 보인 데 비해, 제안 모델은 최고 74.3%의 식별 성능을 보여주었다. 종합 성능 평가를 통해 측정된 모든 지표에서, 제안 모델이 기존의 ED와 DTW에 비해 우수한 성능을 보임을 확인하였다.